Storytelling and market research : a practical user guide - John, C. Frederic (New York, NY : Routledge, 2022)
"Showing how market researchers can get a seat at the decision-making table, this book is the essential guide to mastering storytelling techniques that can dramatically enhance the impact of research reports and presentations, commanding full audience engagement and buy-in. While demand for storytelling in marketing research reports and presentations has mushroomed in recent years, there can be confusion about what decision-makers mean by 'stories.' Leading market research expert Fred John eliminates this confusion by defining four specific types of story in the business arena, and providing a series of 'how-to' guides for generating effective solutions when communicating learning and other information. This book is the first to emphasize the needs of the report reader or presentation audience. Drawing on examples from ancient and modern literature, drama, opera, and other arts, this book will help today's (and tomorrow's) market research professionals to thrive in a world demanding insights, real-world recommendations, and more relevant deliverables"--
Keywords: Marketing research; Business communication; Business presentations; Storytelling; BUSINESS & ECONOMICS / Marketing / Research; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Business Communication / Meetings & Presentations